2020
DOI: 10.32615/bp.2020.082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomic profiling in the roots of salt-tolerant and salt-intolerant maize cultivars treated with NaCl stress

Abstract: Maize crops are sensitive to NaCl stress, which is one of the most harmful abiotic stresses affecting agricultural productivity. To gain further insights into the differential metabolic responses to NaCl stress, we employed metabolomics and physiological approaches to understand the response of salt-tolerant (PH6WC) and sensitive (PH4CV) cultivars of maize. Salt stress caused a significant reduction in root growth, lower root numbers, softened roots, leaf etiolation, inhibition of leaf formation, and decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…This metabolite has also been upregulated in Atriplex halimus metabolic profiling when exposed to salinity and drought stress (Alla et al, 2012). Moreover, the comparative metabolome and transcriptome analysis of different tissues of wheat plants documented the vital role of the upregulation of N-Acetyl-Lphenylalanine in stamen and pistil growth (Yu et al, 2019). These findings suggest that N-Acetyl-L-phenylalanine is another vital metabolite responsible for stress tolerance and several plant developmental stages.…”
Section: General Metabolome Analysis Revealed Stress Responses and Tolerance Mechanisms In Rapeseedmentioning
confidence: 83%
See 1 more Smart Citation
“…This metabolite has also been upregulated in Atriplex halimus metabolic profiling when exposed to salinity and drought stress (Alla et al, 2012). Moreover, the comparative metabolome and transcriptome analysis of different tissues of wheat plants documented the vital role of the upregulation of N-Acetyl-Lphenylalanine in stamen and pistil growth (Yu et al, 2019). These findings suggest that N-Acetyl-L-phenylalanine is another vital metabolite responsible for stress tolerance and several plant developmental stages.…”
Section: General Metabolome Analysis Revealed Stress Responses and Tolerance Mechanisms In Rapeseedmentioning
confidence: 83%
“…In this regard, sugar molecules act as the main signaling molecules and help the movement of nutrients to cope with the current stress environment (Sami et al, 2016). In metabolome analysis, the upregulation of deoxyadenosine has been noted in maize seedlings when exposed to salinity stress (Yue et al, 2020) and in Tibetan hulless barley under CS (Yang et al, 2020).…”
Section: General Metabolome Analysis Revealed Stress Responses and Tolerance Mechanisms In Rapeseedmentioning
confidence: 99%
“…Nucleic acid metabolism was significantly higher in the salt tolerant genotype. Furthermore, some compounds were increased under salinity such as cis-9-palmitoleic acid, L-pyroglutamic acid, galactinol, deoxyadenosine, and adenine [ 256 ].…”
Section: Proteomics Approaches To Identify the Functional And Structu...mentioning
confidence: 99%
“…Various metabolite profiling methods are used to understand the plant molecular responses to drought stress and determine the metabolites’ levels in a specific metabolite pathway or class [ 20 22 ]. The metabolic profile of drought-stressed barley and maize leaves and roots indicated a substantial buildup of metabolites belonging to glyoxylate and dicarboxylate metabolism in maize roots and isoflavonoid biosynthesis in barley roots [ 23 25 ]. Further findings revealed that drought stress tolerance is linked to a signature of metabolites of different metabolic pathways [ 20 ].…”
Section: Introductionmentioning
confidence: 99%